Hypertension in a mountainous province of Vietnam: prevalence and risk factors - Khanh Do Nam; Nhon Bui Van; Long Vo Hoang; Toan Pham Duc; Thu Tran Thi Ha; Viet Tran Tuan; Phong Phan Dinh; Huong Trinh Thi Thu; Pau Loke Show; Vu Thi Nga; Le Bui Minh; Dinh-Toi Chu (Heliyon, 2020)
Background: Hypertension (HTN) significantly contributes to global disease burden, and its prevalence varies amongst different countries and regions. This work is aimed to characterize the hypertensive prevalence and identify risk factors for HTN among the residents in five locations (four communes and one town) of Moc Chau district (Son La province, Vietnam). Methods: A cross-sectional study with a cross-sectional methodology was done in selected places from August 2018 to December 2018. We interviewed 197 participants aged equal to or more than 18 years old and measured their blood pressure (BP). Univariate and multivariate logistic regression were applied. Results: The overall HTN prevalence of 30.0% was recorded. The differences of HTN prevalence rates were seen by several characters including age groups (p <0.001), accompanying disease (p <0.001) and alcohol drinking (p <0.05). Factors independently associated with hypertension were age (ORs: 3.1 [1.1–9.1]; 6.1 [1.7–22.3]), much salty consumption (OR: 2.6 [1.1–6.6]), alcohol use (OR: 3.1 [1.2–8.1]), HTN familial history (OR: 4.2 [1.3–13.3]) and at least one suffering disease (OR: 5.2 [2.1–12.7]). Conclusions: Thus, this study highlighted the high overall HTN prevalence in the Vietnam Northwestern region. Significant differences of HTN rate were observed among several characteristics such as age groups, accompanying disease and alcohol drinking. Age group, much salty consumption, alcohol use, hypertension familial history and at least one suffering disease were risk factors for HTN in study group.